Short-term exposure to ozone and asthma exacerbation in adults: A longitudinal study in China - Fang, Xinyi; Huang, Suijie; Zhu, Yixiang; Lei, Jian; Xu, Yanyi; Niu, Yue; Chen, Renjie (Frontiers in Public Health, 2023)
Background The relationships between short-term ozone exposure and the acute exacerbations of asthma in adults have not been fully studied. Existing studies commonly ignored the effects of ozone on mild or early asthma exacerbations. Objective To investigate the associations between short-term ozone exposure and asthma exacerbations in Chinese adults. Methods We administered health management for adult asthma patients through the Respiratory Home Platform and required them to monitor their lung function every morning and evening by themselves. Finally, a total of 4,467 patients in 18 Chinese cities were included in the current analyses, with 79,217 pairs of lung function records. The maximum daily 8-h average ozone concentrations were collected from fixed-site air quality monitoring stations. We calculated diurnal peak expiratory flow (PEF) variation using morning and evening measurements of PEF and then defined different severity of asthma exacerbations with diurnal PEF variations >10, 15, and 20%, respectively. A binomial distributed generalized additive mixture model combined with distribution non-linear models was applied to examine the association of ozone with asthma exacerbations. We further conducted stratified analyses by sex, age, season of lung function tests, and region. Measurements and results We found that short-term ozone exposure was independently associated with an elevated risk of asthma exacerbations defined by lung function and the effects could last for about 2 days. At lag 0–2 days, each 10 μg/m3 increment in ozone concentration was associated with odds ratios of 1.010 [95% confidence interval (CI): 1.003, 1.017], 1.014 (95% CI: 1.005, 1.023), and 1.017 (95% CI: 1.006, 1.028) for asthma exacerbations that were defined by diurnal PEF variation over 10, 15, and 20%, respectively. The associations remained significant after adjusting for other pollutants, and became unstable when using 24-h average ozone concentration. We also found that the associations were relatively stronger in males, those aged 45 years and older, and in the warm season. Conclusions Our results suggest that short-term ozone exposure can increase the risk of asthma exacerbations, even in the early stage of exacerbation. Male and older asthma patients may be more vulnerable to ozone air pollution, especially in the warm season.